SMEs Capital Budgeting Practices: A Review Article - Al Wahaibi, Mahmood Ali Khalfan; Hussainy, Syed Sadullah; Rajan, Renga; Younas, Afshan (Journal of Ecohumanism, 2024)
This study aims to conduct a comprehensive systematic review of the existing literature on capital budgeting practices (CBP) in Small and Medium-Sized Enterprises (SMEs). By analyzing 130 academic publications from 1964 to 2024, we seek to identify key trends, gaps, and emerging themes in this field. Our analysis reveals a substantial body of research focusing on CBP in larger corporations but highlights a significant dearth of studies specifically examining SMEs, particularly in developing economies. Despite the value of existing research, the current review underscores the need for further exploration of CBP within SMEs. A critical area of inquiry is to understand how SMEs’ CBP differs from those employed by large firms and the underlying reasons for these discrepancies. By revealing the unique challenges and opportunities faced by SMEs, this study contributes to the knowledge pertaining to the development of more effective financial management strategies tailored to their specific needs.